PEMBERDAYAAN PEMUDA MILENIAL SEBAGAI UPAYA PENGEMBANGAN ORGANISASI IPNU BARON NGANJUK - Makhmudah, Siti (ABDI MASYARAKAT, 2025)
Youth is the next generation of the stick of leadership of an organization, wether on a large or small scale. Youth has a duty to continue the existence of an organization. The organization is one of the right places to cultivate the potensial of millennial youth so that they can develop positively. One of the right organizations for the realm of millennial youth is IPNU and IPPNU. IPNU IPPNU is the lowest autotomous body in the organizational structure of NU. IPNU IPPNU consists of students with an age range of 12-30 years. Branch leadership is the IPNU IPPNU management level at the village/kelurahan level. In this implementation, the author uses the ABCD (Asset Basic Community Develompent) method with the pocus of development to be achieved on human capital and environmental capital.